DETERMINANT FACTORS OF COMPANY VALUE IN THE MANUFACTURING SECTOR ON THE INDONESIA STOCK EXCHANGE 2017-2019 - Dini Nur Fakhriani, - (2021)
The purpose of this study are to determine the effects of external and internal factors of the value of the company in the manufacturing sector in Indonesia. Firm value are indicators of how the market values the company as a whole. knowing the value of the company is an important consideration to become an investor in the company. Samples amounted to 148 companies. After going through the procedure to choose the best model, then in this study the model used is the fixed effect model, which is then used to analyze the data in this study. The results of the study found that partially the capital structure and profitability has a positive and significant effect on firm value, inflation has a significant negative effect on firm value. Firm size, dividend policy, and interest rates do not has a significant effect on firm value, and simultaneously it is found that capital structure, profitability, firm size, dividend policy, inflation and interest rates has a significant positive effect on firm value. Keywords: capital structure, company size, company growth, profitability, value company